Scandinavian trade unions’ guidelines regarding nurses’ use of social media: a Fairclough-inspired critical discourse analysis - Glasdam, Stinne; Xu, Hongxuan; Gulestø, Ragnhild Julante Andersen; Glasdam, Selma; Stjernswärd, Sigrid (Frontiers in Communication, 2024)
Social media provides nurses with tools to share information, debate healthcare policy and practice issues, and engage in interpersonal interactions. Historically, also in Scandinavia, nurses' trade unions have taken the lead in defining nursing as a profession and supporting nurses in 'conducting good nursing'. However, it is unexplored how trade unions guide nurses in social media use.To explore the explicitly formulated guidance documents provided by Scandinavian nurses' trade unions, specifically focusing on how the trade unions guided nurses' social media use.Trade union guidelines for social media use were searched on the Scandinavian nurses' organisations' websites. A textual discourse analysis inspired by Fairclough's critical approach was conducted. The analysis considered three levels: the social practice level, focusing on connections between the texts and the surrounding society; the discursive practice level, focusing on the processes of production and distribution of the texts; and the textual level, capturing how grammatical formulations and single words work in the (re)construction of social structures.At the social practice level, the trade union documents guiding nurses' social media uses were embedded in platfomised public communication, laws about confidentiality and data protection, and ethical codes for nurses. At the discursive practice level, the guidelines were constructed to support nurses' social media uses in adhering to their profession's ethical principles. The trade unions' implicit and explicit representations of nurses blurred the distinction between nurses as professionals and nurses as private persons. At the textual level, the guidelines tapped into the potential risks of using social media and how nurses ought to act on social media. Unlike the Danish and Swedish trade unions, the Norwegian trade union did not develop specific guidelines for nurses' social media use.The guidelines emphasised risks stemming from social media use that did not adhere to the profession's politically defined guidelines, norms, and values, although nurses' conditions are already framed by the national legislations and ethical standards. The study advocates for the development of guidelines that support beneficial uses of social media in relation to nurses and the nursing profession.